2015
DOI: 10.1007/s00125-015-3727-0
|View full text |Cite
|
Sign up to set email alerts
|

Central GLP-1 receptor signalling accelerates plasma clearance of triacylglycerol and glucose by activating brown adipose tissue in mice

Abstract: Aims/hypothesisGlucagon-like peptide 1 (GLP-1) receptor (GLP-1R) agonism, used in the treatment of type 2 diabetes, has recently been shown to increase thermogenesis via the brain. As brown adipose tissue (BAT) produces heat by burning triacylglycerol (TG) and takes up glucose for de novo lipogenesis, the aim of this study was to evaluate the potential of chronic central GLP-1R activation by exendin-4 to facilitate clearance of lipids and glucose from the circulation by activating BAT.MethodsLean and diet-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
93
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 114 publications
(102 citation statements)
references
References 32 publications
5
93
1
3
Order By: Relevance
“…Moreover, others have demonstrated that acute activation of central nervous system (CNS) GLP-1Rs promotes BAT thermogenesis and WAT browning [36][37][38]. However, browning of WAT induced by CNS infusion of GLP-1R agonist was abolished in mice with diet-induced obesity [36,38]. We observed that chronic peripheral treatment with GLP-1R agonist promoted the browning of WAT in diet-induced obese mice.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Moreover, others have demonstrated that acute activation of central nervous system (CNS) GLP-1Rs promotes BAT thermogenesis and WAT browning [36][37][38]. However, browning of WAT induced by CNS infusion of GLP-1R agonist was abolished in mice with diet-induced obesity [36,38]. We observed that chronic peripheral treatment with GLP-1R agonist promoted the browning of WAT in diet-induced obese mice.…”
Section: Discussionmentioning
confidence: 59%
“…Our data A clinical study revealed that a dipeptidyl peptidase-4 (DPP-4) inhibitor that decreases endogenous GLP-1 degradation augmented adipose tissue lipolysis and the rate of systemic lipid oxidation in type 2 diabetic patients [35]. Moreover, others have demonstrated that acute activation of central nervous system (CNS) GLP-1Rs promotes BAT thermogenesis and WAT browning [36][37][38]. However, browning of WAT induced by CNS infusion of GLP-1R agonist was abolished in mice with diet-induced obesity [36,38].…”
Section: Discussionmentioning
confidence: 75%
“…Interestingly, both an increase and decrease in metabolic rate have been reported, making it difficult to predict the actions of the endogenous GCG neuronal system. Chronic GLP-1 infusion into the CNS has been shown to lead to transcriptional activation of iBAT and glucose/triglyceride uptake (49,58) resulting from an increase in sympathetic outflow driven by GLP-1R signaling. Other data, however, have shown that the GLP-1R agonist EX-4 can also produce a lowering of VO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Hormoni digestivnog trakta poput GLP-1 posreduju efekte na unos hrane, potrošnju energije i infl amaciju. GLP-1 receptorski signaling aktivira BAT i promoviše braonizaciju WAT-a (19,20), dok GLP-1 takođe smanjuje infi ltraciju makrofazima i infl amatorni signaling u belim adipocitima i makrofagima (21,22). Druge hormonalne promene, kao što je menopauza, takođe utiču na energetski metabolizam.…”
Section: Uloga Braon I Bež Masnog Tkivaunclassified
“…Gut hormones such as GLP-1 mediate effects on food intake, energy expenditure and inflammation. GLP-1 receptor signaling activates BAT and promotes beiging of WAT (19,20) while GLP-1 also reduces macrophage infiltration and inflammatory signalling in white adipocytes and macrophages (21,22). Other hormonal changes such as menopause also affect energy metabolism.…”
Section: The Role Of Brown and Beige Adipose Tissuementioning
confidence: 99%